Applications of the Qur'an in Smartphones According to the Perspective of Fiqh - Imran, Helmi; Bahri, Saiful; Amiruddin, Amiruddin (Budapest International Research and Critics University, 2021)
Technological progress is a necessity faced by humans, because human intelligence has succeeded in creating various devices that are increasingly displaying the sophistication of the previous form. Its presence has had a major influence on the system of human life, where the role of these communication tools has been able to shift some of the roles of humans, and users are increasingly pampered with various applications and features that provide various conveniences for them in carrying out their daily activities. Previously, humans needed to use time specifically to buy food, for example, with the presence of smartphones, they only needed to open an application that served as a delivery person for goods and food. Then order the desired food then in a few moments the food will be delivered to the address without the need to go to a restaurant or stall. This is an example of consumers being spoiled by smartphones that are present in the current era. In addition to having applications and features that can help humans in their daily needs, smartphones also do not forget applications related to human spiritual activities. The developers continue to create and improve various applications that can help humans get closer to their Lord even though they are in places that are not specifically provided for worship. If previously a Muslim wanted to read the Qur'an for example, they needed to bring the Qur'an in the form of a special Mushaf or they needed to go to a special place such as a mosque, surau or other. With the presence of a smartphone, they only need to open the Qur'an application and can read it immediately. The problem that arises then is that the writing of the verses of the Qur'an must be respected by Muslims, then whether the writing of the verses of the Qur'an in smartphones is considered the same as the writings in the manuscripts. This is what makes the writer interested in studying this problem in a relatively short article by referring to the standard fiqh provisions.